2019
DOI: 10.1001/jamapsychiatry.2018.2546
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition vs Individual-Specific Processes in the Association Between Psychotic-like Experiences and Cannabis Use

Abstract: Importance: Previous research indicates that cannabis use is associated with psychotic-like experiences (PLEs). Yet is unclear whether this relationship is due to predispositional (i.e., shared genetic) or individual-specific (e.g., causal processes, such as cannabis use leading to PLEs) factors. Objective: To estimate genetic and environmental correlations between cannabis use and PLEs, and to examine PLEs in twins/siblings discordant for exposure to cannabis use to disentangle predispositional from individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 69 publications
3
30
0
2
Order By: Relevance
“…According to a 2019 study by Karcher et al, individuals who reported frequent lifetime cannabis use (defined as cannabis use >100 times lifetime) were diagnosed with a cannabis use disorder (CUD) and those who reported current cannabis use had an increased risk of 1.21 to 1.26 times of at least one psychotic-like experience. Moreover, psychotic-like experiences were associated with frequent cannabis use (β = 0.11, 95% CI 0.08-0.14), cannabis use disorder (β = 0.13, 95% CI 0.09-0.16), and current cannabis use (β = 0.07, 95% CI 0.04-0.10), even after adjustment for covariates (P < 0.05) [46]. Leadbeater and colleagues (2019) reported that more frequent cannabis use (β = 0.13, 95% CI 0.002-0.25, P < 0.05), as well as CUD (β = 0.51, 95% CI 0.01-1.01, P < 0.05), during adolescence were associated with psychotic symptoms at ages 22 and 23 [47].…”
Section: Patterns Of Cannabis Usementioning
confidence: 96%
“…According to a 2019 study by Karcher et al, individuals who reported frequent lifetime cannabis use (defined as cannabis use >100 times lifetime) were diagnosed with a cannabis use disorder (CUD) and those who reported current cannabis use had an increased risk of 1.21 to 1.26 times of at least one psychotic-like experience. Moreover, psychotic-like experiences were associated with frequent cannabis use (β = 0.11, 95% CI 0.08-0.14), cannabis use disorder (β = 0.13, 95% CI 0.09-0.16), and current cannabis use (β = 0.07, 95% CI 0.04-0.10), even after adjustment for covariates (P < 0.05) [46]. Leadbeater and colleagues (2019) reported that more frequent cannabis use (β = 0.13, 95% CI 0.002-0.25, P < 0.05), as well as CUD (β = 0.51, 95% CI 0.01-1.01, P < 0.05), during adolescence were associated with psychotic symptoms at ages 22 and 23 [47].…”
Section: Patterns Of Cannabis Usementioning
confidence: 96%
“…Cannabis use has been repeatedly associated with the continuum of psychotic experiences, ranging from subthreshold psychotic symptoms to clinical high risk for psychosis. It has been demonstrated that PLEs are more prevalent among cannabis users in the general population when compared to nonusers [19][20][21][22][23][24]. Moreover, there is a dose-response relationship between the frequency of cannabis consumption and increased risk for psychosis [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The associations between drug use and adult outcomes we observed might be direct, indirect or due to confounding. In support of a direct effect, discordant twin studies have found the cannabis-using twin was more likely to use other illicit drugs at a later date 6 7 and report psychotic-like experiences, 25 than the twin who did not. In the Christchurch birth cohort, associations between cannabis use with juvenile offending were attenuated after adjusting for affiliation with substance using or delinquent peers.…”
Section: Discussionmentioning
confidence: 99%